Automated mineralogy (SEM-EDS) approach to sandstone reservoir quality and diagenesis - Worden, Richard H.; Utley, James E. P. (Frontiers in Earth Science, 2022)
Porosity and permeability in sandstones define the reservoir quality and they are controlled by primary sedimentary characteristics and subsequent diagenetic modification. Grain size, sorting, detrital mineralogy, and matrix content are defined at the point of deposition. Bioturbation, infiltration, continued alteration of reactive minerals and soft sediment deformation can occur soon after deposition and, together with the primary characteristics, these condition, or define, how a sediment will behave during subsequent burial. Diagenetic modifications include compaction, initially mechanical and then chemical, mineral growth and, in some cases, grain dissolution and development of secondary pores. Porosity and permeability typically decrease as diagenesis progresses. Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS) approaches can be applied to study many aspects of sandstone diagenesis including detrital mineralogy, grain size, sorting, grain shape, grain angularity and matrix content. SEM-EDS is also useful for defining quantities and location in the pore network of cements that are mineralogically distinct from detrital grains (e.g., calcite, dolomite, siderite, or anhydrite). SEM-EDS can be useful for studying clay mineral cements, especially when they occur in patches bigger than 5 to 10 m. In sandstones, SEM-EDS is not so useful when the cements are mineralogically identical to detrital grains (e.g., quartz cement in quartz sandstones) where additional signals such as cathodoluminescence (CL) may be required . Macro- and meso-pores can be quantified using SEM-EDS but, on its own, it cannot automatically measure micro-porosity as it is below the minimum 1 µm spatial resolution of the approach. Mechanical compaction, a key process that causes porosity-loss in sandstones, is not easily quantified using SEM-EDS. Together with additional routine techniques, SEM-EDS can be used to solve most problems associated with sandstone diagenesis and reservoir quality.